Tuna Fisheries - World Bank; Nicholas Institute (World Bank, Sydney, 2017)
This is a background paper to the Pacific Possible report. The Pacific Island countries control one of the World's largest and healthiest tuna stock. They have been able to significantly increase revenue from fisheries licenses over the past few years through the introduction of the Vessel Day Scheme in the context of the Parties to the Nauru agreement. This report outlines how the Pacific Island countries can further increase benefits from oceanic fisheries without increasing total catch or threatening the sustainability of Pacific tuna fish stocks.